The effect health education with audio visual media on the level of knowledge as an effort to prevent pre-eclampsia in pregnant women - Nugraha, Nareswari; Remedina, Gipfel; Nataningtyas, Candra Dewi (Institute of Accounting Research and Novation (IARN), 2023)
Pre-eclampsia is a pregnancy-related disease characterized by hypertension, edema, and proteinuria. Pregnancy-related problems may arise that are caused directly by hypertension. Pregnant women can prevent preeclampsia by increasing their understanding through health education with audio-visual media to increase their knowledge. This research aims to determine the effect of health education using audio-visual media on the level of knowle1dge in an effort to prevent pre-eclampsia in pregnant women. This research uses a pre-experimental design with research methods pre-test-post test with one group design. Data collection was carried out usiing a questionnaire. Sampling method: non-probability sampling by using techniques A total sample 37 respondents was obtained. The data were analyzed using tests. Wilcoxonsigned rank. The results showed that the level of knowledge about pre-eclampsia prevention before and after health education was valuable p-value = 0.000, which means the value of p < 0.05, then H 1 is accepted, so it can be concluded from this research that there is an influence of health education using audio-visual media regarding pre-eclampsia preventive efforts on the knowledge of pregnant women.